Evaluating the novel coronavirus infection outbreak surveillance results in a state hospital: A retrospective study - Dirgar, Ezgi; Tosun, Betül; Berşe, Soner; Tosun, Nuran; Tosun, Nuran (Makerere University, Medical School, 2021)
Background: Coronavirus disease (COVID-19) has raised the global public health concern and has been declared a pandemic by the World Health Organization. Objectives: This study was aimed to examine the clinical course and outcomes of the patients with COVID-19 in the southeastern part of Turkey. Methods: This retrospective study was conducted on the files of 173 patients who were diagnosed with COVID-19. The “COVID-19 Case Information Form” in the patients’ medical records was used. Results: Of the patients with COVID-19, 64.2% were male and 16.2% had a chronic disease. Their mean age was 34.76±25.75 years. Cough and fatigue were the most common clinical symptoms at admission with 38.7%. The patients at the age of 65 and over were treated mostly in the intensive care unit, and the symptoms associated with the cardiovascular and nausea and vomiting were observed more often (p<0.05). Conclusions: It was found that the majority of the patients were male and there were differences between the age groups in terms of transmission route, the clinic where they were being followed-up, some symptoms, and clinical status outcome. It is recommended that multi-center, prospective, experimental, or observational studies with larger samples should be and the patients should be followed-up for longer periods. © 2021 Dirgar E et al.
Keywords: coronavirus; COVID-19; retrospective study; surveillance